1418. Injections and Infections: Understanding Harm Reduction Utilization in a Rural State. (31st December 2020) - Thakarar, Kinna; Murray, Kim; Sankar, Nityasri; Carwile, Jenny; Lucas, F L; Burris, Debra D; Borelli, Timothy J; Pinsky, Robert; Liechty, Cheryl; Smith, Robert P
Abstract: Background: Increasing rates of injection drug use (IDU) associated-infections suggest significant syringe service program (SSP) underutilization. Our study objective is to assess patient knowledge, attitudes, and practices of safe injection techniques and to determine predictors of SSP utilization in a rural state. Methods: This is a fifteen-month cross-sectional study of participants hospitalized with IDU-associated infections at four hospitals in Maine. Data were collected through Audio Computer-Assisted Self-Interview survey and medical record review. Descriptive analyses were performed to characterize injection knowledge, attitudes and practices. The primary outcome was past 3-month SSP utilization, and the main independent variable was self-reported distance to SSP. Secondary outcomes were uptake of clean drug equipment, naloxone, and treatment with medication for opioid use disorder. Logistic regression analyses were performed to identify factors associated with the primary outcome, controlling for gender, homelessness, history of overdose, having primary care physician and distance to SSP. Results: Of the 101 study participants, 62 participants (65%) reported past 3 month SSP utilization, though only 33% used SSPs frequently. Few participants (10%) reported clean needle/syringe use or clean drug equipment use (5%). Forty-eight percent of participants reported naloxone uptake, and 66% of participants were prescribed medication for opioid use disorder prior to admission. Many participants (59%) lived more than 10 miles from an SSP with 18% of participants living in rural areas. Fifty-four percent reported difficulty accessing an SSP. Participants who lived less than 10 miles of an SSP were more likely to use it (adjusted odds ratio 5.47; 95% CI 2.1- 14.3). Conclusion: Our study highlights unsafe injection practices and lack of frequent SSP utilization among people admitted with IDU-associated infections in Maine. Especially given increasing stimulant use in our state and nationally, these results also highlight the need to promote harm reduction even among individuals prescribed medication for opioid use disorder. Particularly in rural areas where patients may live more than 10 miles from an SSP, expansion of harm reduction services should be a priority. Disclosures: All Authors : No reported disclosures